2010
DOI: 10.1590/s0100-72032010000600003
|View full text |Cite
|
Sign up to set email alerts
|

Concentração de alfa-tocoferol no soro e colostro materno de adolescentes e adultas

Abstract: OBJETIVOS: avaliar a concentração de alfa-tocoferol no soro e colostro materno de puérperas adolescentes e adultas e verificar a adequação nutricional de vitamina E do colostro oferecido ao lactente. MÉTODOS: participaram do estudo 72 puérperas, sendo 25 adolescentes e 47 adultas. Foram coletados 5 mL de sangue e 2 mL de colostro em condição de jejum para análise dos níveis de alfa-tocoferol. As amostras foram analisadas por cromatografia líquida de alta eficiência. A adequação nutricional do colostro para a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…These values are acceptable, based on reference values for serum a-TOH concentrations. Similar concentrations were found in other studies (24)(25)(26).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These values are acceptable, based on reference values for serum a-TOH concentrations. Similar concentrations were found in other studies (24)(25)(26).…”
Section: Discussionsupporting
confidence: 92%
“…The lack of correlation between a-TOH in maternal serum with colostrum (r ¼ 0.073, P ¼ 0.440) has been reported (24,27,30,34,40). Dimenstein et al (24) proposed that the absence of correlation between these variables preclude the existence of passive transfer mechanisms during the passage of vitamin E from the mammary gland to the milk, thereby indicating the existence of a transport mechanism in the breast that is independent of plasma concentration. This could be valid because in late pregnancy and at the beginning of lactation, there is a gradual decrease in serum levels of a-TOH, which may explain the considerable increase in a-TOH in colostrum (37,41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Hence the hypothesis that the milk of adolescent mothers may show lower amounts of alphatocopherol than the milk of adult mothers. 12 In the study by Dimenstein et al, 22 there was no difference (p = 0.50) between alpha-tocopherol levels in the colostrum of Brazilian adolescent and adult mothers ( Table 1). The authors emphasize, however, that the mean age for the adolescent mothers was 17.2 ± 1.4 years, which minimizes the impact of menarche on their nutritional status, as it is the proximity between menarche and pregnancy that potentiates such impact.…”
Section: Age and Maternal Socioeconomic Statusmentioning
confidence: 83%
“…12 Moreover, the pregnant adolescent has to add her own growth requirements to other requirements imposed by pregnancy. 22 Therefore, when pregnancy and subsequent lactation occur in adolescence, nutritional risks associated with this condition may increase. Hence the hypothesis that the milk of adolescent mothers may show lower amounts of alphatocopherol than the milk of adult mothers.…”
Section: Age and Maternal Socioeconomic Statusmentioning
confidence: 99%
“…Gurgel et al 8 found a high prevalence of the deficiency in women attended for the delivery in public maternities when compared to those attended at a private health network. Dimenstein et al 9 found no differences in the alpha-tocopherol serum level according to maternal age; and another study also found no differences in this micronutrient in parturient according to age, parity and gestational weight gain. 10 As it is known in the environment, permeated by material conditions of life and by the access to health services and schooling, it determines characteristic patterns of health and disease.…”
Section: Introductionmentioning
confidence: 93%